ANALISIS STABILITAS LERENG AREA KATALA TAMBANG BATU HIJAU KABUPATEN SUMBAWA BARAT - Ali Syahidullah; Dedy Dharmawansyah; Hermansyah (Hexagon Jurnal Teknik dan Sains, 2020)
Reclamation carried out by PT. AMNT in the Katala area of 8.14 hectares consists of 2 parts covering part 1 namely areas A, B and C and part 2 namely areas A and B. In designing the geometry of the mine slope, Geotechnical Engineer should optimize the steepness of the mine slope because this is very affect the stability of a slope. The focus of this study examines influence the slope geometry design on the stability of the slope under the existing conditions in parts 1 areas A and B and 5 slope variation models are added. The purpose of this study was to obtain the value of safety factor using the Fellenius method used GeoStudio 2018 sub-program Slope / W to be recommended as consideration data in analyzing the stability of special slopes in the Batu Hijau mine reclamation activity. The results obtained by the safety factor value in section 1 area A for the existing conditions is 2.483, the variation models I to V obtained successive results of 1.670, 1,297,1,250, 1,041, 0,687, then in section 1 area B obtained the value of the safety factor for the existing conditions is 2,373, variation models I to V are 1,585, 1,254, 1,230, 1,003 0,651. while the manual analysis obtained the value of the safety factor in section 1 area A for existing conditions of 2,410, the variation models I to V successively amounted to 1.576, 1.253, 1.187, 1.020 0.608. In section 1 area B, the safety factor values for the existing conditions is 2,311, the variation models I to V are 1,506, 1,246, 1,182, 0,964 0,587.